Karakteristik Kelainan Hematologi Pasien Systemic Lupus Erythematosus di RSUP Prof. Dr. I.G.N.G. Ngoerah di Poli Rawat Jalan Rematologi - Satwika Hadipratama; Gede Kambayana (PT Dexa Medica, 2025)
Systemic lupus erithematosus (SLE) is one of the leading causes of death among young women. Hematological abnormalities are common manifestations of SLE, and can affect various types of blood cell, with severity ranging from mild to life-threatening. The main hematological manifestations of SLE include anemia, leucopenia, thrombocytopenia, lymphadenopathy, and/or splenomegaly. This study aims to explore the characteristics of hematological disorders in SLEpatients. Methods: This was a retrospective descriptive study using a cross-sectional data collection method. The subjects were patients diagnosed with SLE who received treatment at RSUP Prof. dr. I.G.N.G. Ngoerah, Denpasar, during the period of July–August 2023. Results: A total of 72 subjects participated in this study, with a mean age of 35.9 years (range: 18–72 years). The majority were female (90.3%) and were within the 18–50 year age group (87.5%). Laboratory tests showed the following mean values: hemoglobin 11.8 g/dl, platelets 299.5×10³/μl, white blood cells (WBC) 13.5×10³/μl, lymphocytes 1.7×10³/μl, and erythrocyte sedimentation rate (ESR) 32.6 mm/hour. The mean neutrophil-to-lymphocyte ratio (NLR) was 3.92. The mean values of renal function and metabolic parameters were as follows: blood urea nitrogen (BUN) 13.3 mg/dl,serum creatinine (SC) 1.19 mg/dl, estimated glomerular filtration rate (eGFR) 100 ml/minute/1.73 m², protein-to-creatinineratio (PCR) 1.03, and calcium level 9.2 mg/dl. Bone mineral density measurements revealed that 6.9% of subjects had osteopenia and 9.7% had osteoporosis. Conclusion: This study provides a better understanding of the clinical, laboratory,and comorbidity profile of patients with SLE. These findings offer valuable insights for appropriate clinical management and intervention strategies.